Firefighter observations on mountain pine beetle post-outbreak lodgepole pine fires: expectations, surprises and decision-making - Moriarty, Kevin, author; Cheng, Antony S., advisor; Hoffman, Chad, committee member; Cottrell, Stuart, committee member (Colorado State University. Libraries, 2014)
Recent wildfires in mountain pine beetle (Dendrocronas ponderosae; MPB) post-outbreak lodgepole (pinus contorta var. latifolia) stands in the western United States have generated concern among stakeholders and disagreement over predicted fire behavior in the scientific literature. A study was conducted of wildland firefighters' observations of fire behavior in beetle-killed lodgepole pine forests to garner a better understanding of expected vs. observed fire behavior, with a focus on what fire behaviors surprised firefighters. Twelve MPB post-outbreak wildfires and one prescribed fire were identified in northern Colorado and southern Wyoming using USDA aerial surveys, USGS MODIS based perimeter mapping and local knowledge. Twenty-eight wildland firefighter interviews were conducted among 7 different federal, state, county, local and non-profit agencies with a total of 55 observations. Expectations, observations, surprising fire behavior and tactical decisions were categorized using qualitative coding and interpretation. Expectations were greatly based on prior wildland fire experiences rather than the scientific research results. Surprising fire behavior in the red phase included increased fire behavior in moderate conditions, increased spotting, faster crown fire transition and crown fire transition with limited or no ladder fuels. Surprising fire behavior in the grey phase included crown ignition and crown fire propagation. Observations support the increased fire behavior in MPB post-outbreak red phase and diverge from studies predicting reduced crown fire potential in red and mixed phases. Firefighters formed new expectations of active fire behavior potential in all weather conditions and MPB phases. However, respondents concluded that specific conditions of fuel, weather and topography are the main driving forces in fire behavior and MPB influence was limited to distinct events. Firefighters changed tactics by taking more indirect suppression approaches due to fire behavior and tree hazard.
Keywords: firefighter observations; surprising fire behavior; mountain pine beetle